The jaw‐dropping costs of oral cavity cancer malpractice. Issue 10 (29th May 2021) - Wong, Amanda; Zhu, Daniel; Tong, Jane Y.; Ko, Andrew; Tham, Tristan; Kraus, Dennis
Abstract: Background: Medical litigation is different than it was 20 years ago due to changes in health care. This study provides an updated analysis of oral cavity malpractice litigation from the past two decades (2000–2010 and 2011–2019). Methods: Verdict reviews from the Westlaw database were analyzed from January 2000 to August 2019. Data were collected and analyzed with the Statistical Package for the Social Sciences. Results: Sixty‐five lawsuits were evaluated across 24 states. Failure to diagnose was the most common allegation in both decades. Adjusting for inflation, the average amount awarded from 2000 to 2010 was $1 721 068 and $3 925 504 from 2011 to 2019. Conclusions: There has been a significant rise in allegations of failure to biopsy and failure to refer ( p  < 0.05). In addition, while award amounts appear different between decades, the difference is not statistically significant ( p  = 0.248). Education should focus on early diagnosis, biopsy, and referral to physicians who routinely care for this patient population.